(untitled) (Gaceta Técnica, 2018)
The objective proposed in this work was to find out if there is a relationship between the beginning of summer time in Mexico and the number of road accidents, since the entrance of such schedule causes fatigue, which is reported as a cause of accidents. The permutations test was used and there was no evidence of an increase in accidents associated with the entry of summer time. The limitations of the study are, on the one hand, the lack of accident records prior to the implementation of summer time and, on the other, not having controlled the time of occurrence of the accidents analyzed; in future cases it is recommended to control this last variable. Summer time in Mexico was implemented since 1996 and its effects on road traffic accidents had not yet been studied; the originality of the present study lies in studying such effects. The findings suggest that vehicular driving with natural light provides greater safety even when the driver is fatigued